Parsimonious versus extensive bleeding score: can we simplify risk stratification after percutaneous coronary intervention and reduce bleeding events by de-escalation of the antiplatelet strategy? - Pascal Vranckx; Stephan Windecker; Marco Valgimigli; Neil O’Leary; Yoshinobu Onuma; Peter Damman; Eva Christine Ida Woelders; Kai Ninomiya; Denise Adriana Maria Peeters; Arnoud Willem Johannes van 't Hof; Patrick Washington J C Serruys; Robert-Jan Matthijs van Geuns (Open Heart)
Background and aims Due to the multitude of risk factors outlined in the guidelines, personalised dual antiplatelet therapy (DAPT) guidance after percutaneous coronary intervention (PCI) is complex. A simplified method was created to facilitate the use of risk stratification. We aimed to compare the predictive and prognostic value of the ‘Zuidoost Nederland Hart Registratie’ (ZON-HR) classification for bleeding risk with the PREdicting bleeding Complications In patients undergoing Stent implantation and subsEquent DAPT (PRECISE-DAPT) score and to determine the effect of ticagrelor monotherapy versus DAPT in patients with or without high bleeding risk (HBR).Methods A post hoc analysis of the GLOBAL LEADERS trial was performed to compare the predictive value of the ZON-HR classification with the PRECISE-DAPT score. Also, the outcomes stratified by either method were compared and the interaction of HBR on the treatment effect was determined.Results The required parameters for the ZON-HR classification (3.7% HBR) and PRECISE-DAPT score (16.6% HBR) were available in 99.9% and 93% of the patients, respectively. The ZON-HR classification had a lower sensitivity (0.09 vs 0.26) and a higher specificity (0.97 vs 0.84), positive predictive value (0.13 vs 0.08) and accuracy (0.92 vs 0.82). Regression analysis showed that both methods predicted hazard for bleeding risk with HRs of 1.87 (95% CI: 1.59 to 2.18) and 2.67 (95% CI: 2.10 to 3.41) for the PRECISE-DAPT score and ZON-HR classification, respectively. The omission of aspirin reduced bleeding events only in acute coronary syndrome (ACS) patients without HBR (HR: 0.74, 95% CI: 0.61 to 0.90, p value for interaction of HBR: 0.04).Conclusions Stratification for bleeding risk according to the ZON-HR classification was feasible in almost all patients and showed to be more conservative than the PRECISE-DAPT score with a consistent prognostic accuracy. The benefit of aspirin omission was the largest in ACS patients without HBR.Trial registration number NCT01813435.